High risk of coronary artery aneurysm in Kawasaki disease. (5th November 2020) - Mossberg, Maria; Mohammad, Aladdin J; Kahn, Fredrik; Segelmark, Mårten; Kahn, Robin
Abstract: Objective: Kawasaki disease (KD) is a vasculitis of unknown aetiology with a high risk of coronary aneurysms if untreated. Timely treatment with intravenous immunoglobulin decreases the risk for coronary artery aneurysms (CAA). In this study, we set out to elucidate the factors associated with the risk of developing CAA. Methods: Records of all KD-diagnosed children in Skåne between 2004 and 2014 were collected and clinical and demographic data were compiled. KD is defined according to the revised American Heart Association diagnostic criteria and classified as either complete KD (cKD) or incomplete KD (iKD). Results: KD was diagnosed in 77 children and CAA was found in 31% ( n = 24). Children with CAA were younger compared with children without (median; 20 vs 34 months) and intravenous immunoglobulin treatment within 10 days was less likely to be received (75% vs 91%). In children presenting with iKD, 47% developed CAA compared with 21% in cKD patients. Using multivariate analysis, an association between the risk of CAA with low age in children with iKD was observed. Conclusion: The risk of CAA development is disturbingly high in young children with iKD. This highlights the importance of rapid intense treatment and vigilance in infants, who are the most difficult to diagnose, in order to reduce the frequency of CAA.